Clinical analysis and literature review of two paediatric cases of anti-IgLON5 antibody-related encephalitis - Feng, Mei; Zhou, Zhen; Kang, Qingyun; Wang, Miao; Tang, Jingwen; Wu, Liwen (Frontiers in Neurology, 2024)
Introduction Anti-IgLON5 antibody-related encephalitis is a rare autoimmune disorder of the central nervous system, predominantly occurring in middle-aged elderly individuals, with paediatric cases being exceptionally rare. This study aims to enhance the understanding of paediatric anti-IgLON5 antibody-related encephalitis by summarising its clinical and therapeutic characteristics. Method A retrospective analysis was conducted on two paediatric patients diagnosed with anti-IgLON5 antibody-related encephalitis at Hunan Children’s Hospital from August 2022 to November 2023. This involved reviewing their medical records and follow-up data, in addition to a literature review. Results The study involved two patients, one male and one female, aged between 2.5 and 9.6 years, both presenting with an acute/subacute course of illness. Clinically, both exhibited movement disorders (including dystonia, involuntary movements, and ataxia), cognitive impairments, sleep disturbances, and psychiatric symptoms. Patient 1 experienced epileptic seizures, while Patient 2 exhibited brainstem symptoms and abnormal eye movements. Neither patient showed autonomic dysfunction. Patient 1 had normal cerebrospinal fluid (CSF) and Brain MRI findings, whereas Patient 2 showed moderate leukocytosis and mild protein elevation in the CSF, and Brain MRI revealed symmetrical lesions in the basal ganglia and cerebellum. Oligoclonal bands in the CSF were positive in both cases. Both patients tested negative for HLA-DQB*05:01 and HLA-DRB*10:01. They received both first-line and second-line immunotherapies, with Patient 2 showing a poor response to treatment. Discussion Paediatric cases of anti-IgLON5 antibody-related encephalitis similarly present sleep disturbances as a core symptom, alongside various forms of movement disorders. Immunotherapy is partially effective. Compared to adult patients, these paediatric cases tend to exhibit more pronounced psychiatric symptoms, a more rapid onset, and more evident inflammatory changes in the CSF. The condition appears to have a limited association with HLA-DQB*05:01 and HLA-DRB*10:01 polymorphisms.